Molecular and genomic insights into multidrug-resistant (MDR) and extensively drug-resistant (XDR) Pseudomonas aeruginosa causing burn wound infections in Bangladesh - Spencer Mark Mondol; Md. Rafiul Islam; Md. Elias Mia; Md. Hasibul Hassan; Fardin Farhad; Kalpona Akter; Shahriar Kabir Shakil; Israt Islam; Nadira Naznin Rakhi; Jannatul Ferdous Mustary; Amiruzzaman; Md. Mizanur Rahaman (Scientific Reports)
Abstract The emergence of multidrug-resistant (MDR) and extensively drug-resistant (XDR) Pseudomonas aeruginosa represents a significant challenge in managing nosocomial infections, particularly in vulnerable populations such as burn patients. This study provides genomic and molecular characterization of MDR and XDR P. aeruginosa strains isolated from burn patients at Sheikh Hasina National Institute of Burn and Plastic Surgery (SHNIBPS) in Dhaka, Bangladesh. Over an 8-month period, 110 wound swabs were collected, with 91 isolates identified as P. aeruginosa. Antimicrobial susceptibility testing demonstrated a multidrug-resistant pattern in 30 isolates and an extensive drug-resistant pattern in the remaining 61 isolates analyzed in this study. PCR assays detected beta-lactamase genes from all four Ambler classes, revealing a notable prevalence of bla NDM-1 (16.48%) and bla VIM-2 (31.87%), with both genes co-occurring in 3.30% of the isolates. Additionally, bla PER-1 (15.38%), bla CTX-M (4.40%), bla OXA-1 (84.62%), and bla OXA-48 (51.65%) genes were detected. Class I integrons were detected in 84 isolates. A total of 21% of the isolates exhibited strong biofilm-forming capabilities. Key biofilm-associated genes (pelB, pilT, rhlB) were detected in most of the isolates. Whole genome sequence analysis of two selected XDR isolates identified different beta-lactamase genes such as bla PDC-98, bla PDC-374, bla OXA-50, bla OXA-677 and bla OXA-847. Virulence factor genes, metal resistance genes, and prophage sequences were also identified in the analysis. The genomic epidemiology analysis of 9,055 P. aeruginosa strains, based on MLST data, revealed the dominance of ST235. The bla PDC and bla OXA genes were found to be notably prominent worldwide. The comparative genomic analysis of P. aeruginosa strains from Bangladesh demonstrated an expanding pangenome as well as high degree of genetic variability. The study emphasized the dynamic nature of the P. aeruginosa pangenome and underscored the necessity for stringent infection control measures in burn units to manage and mitigate the spread of these highly resistant strains.